Southern Gothic Literature - Ellis, Jay, 1963- (Ipswich, Massachusetts : Salem Press, a division of EBSCO Publishing ; Amenia, NY : Grey House Publishing, 2013)
"American Southern Gothic Literature presents one of the few book-length surveys of the genre available today, in a diverse collection of representative texts from a group of international critics. In addition to exemplary novels from established writers, such as Edora Welty, Flannery O'Conner, Carson McCullers, and Cormac McCarthy, works explored here include poetry, a play, and a fairy tale novella. This volume, part of the Critical Insights series, offers a collection of original essays that will establish for students and their teachers an exemplary representation of the genre Southern Gothic as a field of study within American literature. Edited by Dr. Jay Ellis, Senior Instructor at the University of Colorado-Boulder, recognized as one of the leading authorities in Cormac McCarthy criticism, this volume seeks to extend the scope and diversity of literature that constitutes the genre, drawing upon representative themes, grounded in the diverse, often troubled history of the South, while introducing new perspectives and twists to the form, such as in the work of zombie literature as a generative trope. The introduction of poetry, in readings on Allen Tate, James Dickey, and Donald Justice, among others, into what has been a genre defined by fiction represents the originality of the volume. This collection will also consider the geographical significance of the genre within the broader field Southern literature. Defining genres remains a complex task, and these chapters will provide for readers the constitutive terms to locate, both geographically and metaphorically, the Southern Gothic."--Publisher's website.
On southern gothic literature -- Critical Contexts. Defining southern gothic -- "Dark legacy": gothic ruptures in southern literature -- Flannery O'Connor and Harry Crews get naked -- The road beyond zombies of the new south -- Critical readings. Charles W. Chesnutt's southern gothic of guilt -- Revealing Faulkner: religious fall in The sound and the fury -- Carson McCullers' Boardinghouse and the architecture of ruin -- "Southern fried fairy tales": Eudora Welty's The robber bridegroom -- Sexuality, insanity, and the old South in Tennessee Williams's Suddenly last summer -- "Fantastic terrors never felt before": southern gothic poetry -- Cthulhu visits the south, or Fred Chappell's Three levels of dagon -- Gothic fear and anxiety in Cormac McCarthy's Suttree -- "Anything dead coming back to life hurts": the double murder of Beloved.
Includes bibliographical references (pages 267-269) and index.
Keywords: Gothic fiction (Literary genre), American -- History and criticism; American fiction -- Southern States -- History and criticism; Gothic revival (Literature) -- Southern States; Horror tales, American -- History and criticism